Integrasi Pendidikan Islam dalam Pembelajaran Tematik sebagai Upaya Penguatan Profil Pelajar Pancasila di Sekolah Dasar - Noptario Noptario; Mamkua Mamkua; Sedya Santosa (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Thematic learning is very intense learning taught in class. This makes the thematic lessons properly taught by the teacher. One way that teachers can do to achieve learning goals in thematic subjects is to integrate thematic lessons and Islamic Education. The purpose of this study is to describe the implementation of Islamic education in thematic learning as an effort to strengthen the profile of Pancasila students in elementary schools in one of the cities of Palmebang. This type of research is a type of qualitative research approach. Sources of data in this study were obtained through interviews. Interviews were conducted with two informants consisting of class 2 thematic teachers and class 3 thematic teachers. This research was conducted in the even semester of the 2022/2023 academic year. Thematic learning that is integrated with Islamic Education is in line with the program to strengthen the Pancasila student profile. This is because the aspects contained in the Pancasila student profile are an illustration of the character taught through thematic learning and also taught by religious teachings. Therefore if students get thematic lessons that are integrated with Islamic Education, then students will get knowledge from two disciplines.